Predicting Alcohol Dependence Symptoms by Young Adulthood: A Co-Twin Comparisons Study. (16th August 2021) - Stephenson, Mallory; Barr, Peter; Aliev, Fazil; Ksinan, Albert; Latvala, Antti; Vuoksimaa, Eero; Viken, Richard; Rose, Richard J.; Kaprio, Jaakko; Dick, Danielle; Salvatore, Jessica E.
Abstract: Co-twin comparisons address familial confounding by controlling for genetic and environmental influences that twin siblings share. We applied the co-twin comparison design to investigate associations of adolescent factors with alcohol dependence (AD) symptoms. Participants were 1286 individuals (581 complete twin pairs; 42% monozygotic; and 54% female) from the FinnTwin12 study. Predictors included adolescent academic achievement, substance use, externalizing problems, internalizing problems, executive functioning, peer environment, physical health, relationship with parents, alcohol expectancies, life events, and pubertal development. The outcome was lifetime AD clinical criterion count, as measured in young adulthood. We examined associations of each adolescent domain with AD symptoms in individual-level and co-twin comparison analyses. In individual-level analyses, adolescents with higher levels of substance use, teacher-reported externalizing problems at age 12, externalizing problems at age 14, self- and co-twin-reported internalizing problems, peer deviance, and perceived difficulty of life events reported more symptoms of AD in young adulthood ( p s < .044). Conversely, individuals with higher academic achievement, social adjustment, self-rated health, and parent–child relationship quality met fewer AD clinical criteria ( p s < .024). Associations between adolescent substance use, teacher-reported externalizing problems, co-twin-reported internalizing problems, peer deviance, self-rated health, and AD symptoms were of a similar magnitude in co-twin comparisons. We replicated many well-known adolescent correlates of later alcohol problems, including academic achievement, substance use, externalizing and internalizing problems, self-rated health, and features of the peer environment and parent–child relationship. Furthermore, we demonstrate the utility of co-twin comparisons for understanding pathways to AD. Effect sizes corresponding to the associations between adolescent substance use, teacher-reported externalizing problems, co-twin-reported internalizing problems, peer deviance, and self-rated health were not significantly attenuated ( p value threshold = .05) after controlling for genetic and environmental influences that twin siblings share, highlighting these factors as candidates for further research.